Surya Buana Senior High School Strategy in Facing Competition in The Era of Globalization - Fahmi, Ahmad Khoirur Rijal (Faculty of Education Universitas Negeri Malang, 2022)
This research aims to determine the educational strategy of SMA Surya Buana in facing competition in an era that describes globalization. Researchers used a descriptive approach method. The research results found were Surya Buana High School educational strategies, including: (a) analyzing the internal and external environment through SWOT analysis; (b) Formulation of the vision and mission of educational institutions; (c) Determine the long-term and short-term goals of the educational organization; (d) Designing policies in educational institutions for the decision-making process; (e) Strategic planning of educational organization programs; and (f) Design of each implementation process